Mobile phone camera glass processing method

CN122977682APending Publication Date: 2026-10-27DONGGUAN FENGYAO PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611082703.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]为了解决现有摄像头玻璃加工工艺中化学强化压应力闭合及韧性油墨拉扯导致裂片崩边严重、良率低的技术问题,本申请提供了一种手机摄像头玻璃加工方法

Benefits of technology

(1)过在轮廓线区域制备耐高温抗离子交换掩膜,在化学强化时人为制造“应力低谷”,裂片时裂纹被应力梯度精准引导瞬断,彻底消除了压应力闭合裂纹导致的崩边,裂片力降低50%以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a mobile phone camera lens glass processing method and relates to the field of glass processing; the processing method comprises the following steps: cutting a set-depth contour line on a glass base material; preparing a high-temperature-resistant and ion-exchange-resistant mask film to form a shielding belt along the contour line area; removing the mask film after chemical strengthening of the glass base material with the mask film; performing multilayer silk printing on the glass base material, wherein high-fragility ink is adopted for the last layer of full-surface silk printing; and separating the lens product by applying external force along the contour line. According to the method, a stress low valley is manufactured in the contour line area by the shielding belt, the influence of compressive stress on closed cracks is eliminated, and the bridging pulling force during crack separation is eliminated by using high-fragility ink, so that the crack separation force is greatly reduced, the crack separation edge problem is completely solved, and the product yield is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of glass processing, specifically to a method for processing mobile phone camera glass. Background Technology

[0002] As the pixel count of smartphone cameras continues to increase, extremely high requirements are placed on the light transmittance, surface hardness, and appearance yield of camera protective lenses. Currently, the industry generally uses high-alumina silicate glass as the camera lens material, and improves its impact resistance through chemical strengthening. Chemical strengthening replaces sodium ions on the glass surface with potassium ions in high-temperature molten salt, forming strong surface compressive stress on the glass surface.

[0003] Existing high-efficiency processing techniques typically include: material preparation, surface grinding and polishing, laser cutting of contour lines, acid washing, chemical strengthening, full-plate screen printing, and splitting. This process, by completing screen printing on a full-plate glass substrate before splitting, significantly improves production efficiency compared to traditional single-piece screen printing.

[0004] However, the existing processes described above have physical contradictions in actual mass production, making it difficult to overcome the yield bottleneck in the cleaving process. On the one hand, the surface compressive stress formed by chemical strengthening acts on the contour area formed by laser cutting, causing compressive stress on the surface of microcracks. The physical characteristic of compressive stress is to "close" cracks, which means that crack propagation during cleaving must overcome huge compressive stress resistance, making cracks prone to deviation and branching. On the other hand, the conventional tough ink used in full-plate screen printing has high molecular elasticity after curing. During cleaving, the ink does not break but generates bridging and pulling forces on both sides of the glass, further forcing the crack to deviate from the predetermined trajectory, resulting in severe edge chipping. Summary of the Invention

[0005] To address the technical problems of severe chipping and low yield caused by chemically strengthened compressive stress closure and tough ink stretching in existing camera glass processing technology, this application provides a method for processing mobile phone camera glass.

[0006] The first aspect of this application provides a method for processing mobile phone camera glass, including the following steps: cutting a contour line of a set depth on a glass substrate; preparing a high-temperature resistant and ion-exchange resistant mask along the contour line area to form a shielding strip; placing the glass substrate with the mask in molten salt for chemical strengthening; removing the mask from the chemically strengthened glass substrate; performing multi-layer screen printing on the glass substrate, wherein the last layer of full-surface screen printing uses high-brittle ink; applying external force along the contour line to separate and obtain the finished lens.

[0007] Preferably, a picosecond laser is used to cut a contour line of a set depth on the glass substrate.

[0008] Preferably, after cutting out the contour line of the set depth and before preparing the mask, the process further includes a two-step acid washing step of sequentially performing low-concentration acid washing and high-concentration acid washing on the glass substrate.

[0009] Preferably, low-concentration pickling uses hydrofluoric acid with a concentration of 4-6%. Preferably, the width of the shielding strip is 0.1-0.2 mm.

[0010] Preferably, a high-temperature resistant and ion-exchange resistant mask is prepared using photolithography or precision screen printing.

[0011] Preferably, the high-brittleness ink comprises inorganic fillers, resin, and silane coupling agents, wherein the content of inorganic fillers is greater than 60 wt%. The high content of inorganic fillers imparts extremely high brittleness to the ink. Preferably, the inorganic filler is low-temperature glass powder, and the resin is epoxy-modified silicone resin.

[0012] Preferably, the step of removing the mask from the chemically strengthened glass substrate includes: removing the mask by laser stripping or hot alkaline solution immersion, followed by high-pressure rinsing with pure water. Both laser stripping and hot alkaline solution immersion can efficiently and non-destructively remove the mask, while high-pressure rinsing with pure water ensures that no residue affects subsequent screen printing.

[0013] The present invention has the following beneficial effects: (1) By preparing a high-temperature resistant and ion-exchange resistant mask in the contour area, a “stress trough” is artificially created during chemical strengthening. When the sheet is split, the crack is precisely guided by the stress gradient to break instantly, which completely eliminates the edge breakage caused by the compressive stress closed crack and reduces the splitting force by more than 50%.

[0014] (2) The last layer of screen printing uses high brittle ink, which adheres strongly to the glass after curing and has no plastic deformation ability. When the glass cracks, it breaks instantly and synchronously, eliminating the bridging and pulling force generated by conventional tough ink, and preventing edge whitening and micro-cracks caused by ink pulling.

[0015] (3) The two-step pickling process plays a synergistic role under the premise of stress shielding. The low concentration protects the edge size, while the high concentration expands the microcrack opening, further reducing the external force required for the cracked piece, thus achieving a balance between high strength and high yield. Detailed Implementation

[0016] To facilitate understanding of this application, a more complete description will be provided below. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0017] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0018] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0019] It should be noted that, in this application, the "high-temperature resistant ion-exchange mask" refers to a material layer that can stably exist and effectively block the exchange of potassium ions in the molten salt with sodium ions on the glass surface in a chemically strengthened high-temperature molten salt environment (typically KNO3 molten salt at around 400°C). Its core function is physical shielding, preventing ion volume expansion in the covered contour area, thereby preventing the formation of surface compressive stress. Common high-temperature resistant ion-exchange mask materials include, but are not limited to, high-temperature photoresists, ceramic pastes, or inorganic silicate mask materials, which must possess good adhesion to the glass surface and chemical stability, remaining insoluble and non-degradable in high-temperature molten salt.

[0020] The term "highly brittle ink" refers to an ink composition that exhibits extremely low fracture toughness and almost no plastic deformation ability after curing. In this field, conventional inks often use polymer resins (such as polyurethane resins) as film-forming materials, resulting in high elasticity and high elongation at break after curing, which generates bridging tensile forces upon cracking. Highly brittle inks, however, significantly increase the content of inorganic fillers (such as low-temperature glass powder) to over 60 wt%, causing the film-forming material to form a hard and brittle structure similar to a glassy state after curing. Simultaneously, by introducing a silane coupling agent, a strong chemical bond (Si-O-Si bond) is formed between the inorganic filler and the glass substrate, thereby achieving instantaneous and synchronous brittle fracture under stress while maintaining high adhesion, avoiding tensile stress transmitted through the polymer chains.

[0021] The "stress trough" refers to a specific stress distribution state formed within the glass substrate after chemical strengthening. Because the contour area is masked and no potassium-sodium ion exchange occurs, this area retains the low-stress state of the original glass; while the lens body area undergoes normal ion exchange, forming high-pressure stress. A significant stress gradient is formed between the two, and the contour area becomes the "trough" on the stress distribution curve. During cracking, the stress gradient guides the crack to concentrate in the low-stress area (i.e., the contour line) and break instantly, preventing the crack from overcoming closure resistance and shifting in the high-pressure stress area.

[0022] Regarding the synergistic effect of "two-step pickling" and "stress shielding," it is important to clarify the following: Without stress shielding, the contour region is under high-pressure stress, and the microcrack opening is tightly "closed" and locked by the strong compressive stress. At this point, even if high-concentration pickling expands the physical opening of the microcrack, the compressive stress will still close it immediately upon application of force, negating the effect of pickling's widening effect. Therefore, the fracturing force does not change significantly. Only after introducing stress shielding and eliminating the compressive stress closure effect in the contour region, the microcrack is in a freely "open" state. Only then can the two-step pickling's effect of expanding the microcrack opening and increasing stress concentration points substantially reduce the external force required for fracturing. There is a strict synergistic dependency between the two mechanisms.

[0023] This invention provides a method for processing mobile phone camera glass, including the following steps: Cut a contour line of a predetermined depth on a glass substrate; A high-temperature resistant and ion-exchange resistant mask is prepared along the contour area to form a shielding band; A masked glass substrate is placed in molten salt for chemical strengthening; Remove the mask on the chemically strengthened glass substrate; perform multi-layer screen printing on the glass substrate, with the last layer using highly brittle ink; apply external force along the contour line to separate and obtain the finished lens.

[0024] This invention creates a mask in the contour area. During chemical strengthening, potassium ions in the molten salt cannot penetrate the mask to exchange with sodium ions in the contour area. This allows the lens body to undergo normal ion exchange under high pressure, while the contour area maintains the low-stress state of the original glass, keeping microcracks in an "open" state. This is equivalent to artificially creating a "stress trough" inside the glass. When the lens is cracked, the crack is precisely guided by the stress gradient along the trough and breaks instantly, completely eliminating edge chipping caused by compressive stress-induced closed cracks. Simultaneously, the final full-surface screen printing uses highly brittle ink, which, after curing, forms a hard, brittle layer similar to glass with extremely low fracture toughness. When the lens is cracked, once the crack in the glass extends to the surface, the brittle ink breaks instantly and synchronously, eliminating the bridging tensile force generated by conventional tough inks and preventing edge whitening and microcracks caused by ink pulling.

[0025] Specifically, the high-temperature resistant and ion-exchange resistant mask can be selected from any one of high-temperature resistant photoresist, ceramic paste, or inorganic silicate mask material.

[0026] In a preferred embodiment, a picosecond laser is used to cut a contour line of a predetermined depth on the glass substrate. Picosecond laser cutting can form a contour line composed of dense micropores, resulting in a small heat-affected zone, high cutting precision, and facilitating subsequent stress shielding and dicing. Specifically, the laser wavelength can be selected from any of 1030nm and 1064nm, the dot spacing can be selected from any of 3μm, 4μm, 5μm, and 6μm, and the cutting depth can be selected from any of 0.2mm, 0.25mm, and 0.3mm.

[0027] In a preferred embodiment, after cutting the contour line to a predetermined depth and before preparing the mask, a two-step pickling process is included, involving sequential low-concentration pickling and high-concentration pickling of the glass substrate. Low-concentration pickling gently removes the heat-affected zone and molten material from the laser cutting, preventing excessive lateral corrosion; high-concentration pickling utilizes highly reactive ions to rapidly etch at the bottom of the contour line, expanding microcrack openings and creating better stress concentration points. Specifically, the pickling solution can be selected from hydrofluoric acid-based solutions.

[0028] In a preferred embodiment, low-concentration pickling uses hydrofluoric acid with a concentration of 4-6%, and high-concentration pickling uses hydrofluoric acid with a concentration of 10-14%. The high-concentration pickling time is controlled within 1.5 minutes, and the increase in etching depth caused by high-concentration pickling does not exceed 10 μm. Strict control of the high-concentration pickling time and etching depth can expand the microcrack opening while ensuring that the surface bevel size does not exceed the limit, preventing the lateral expansion of the outline from eroding the effective viewing area. Specifically, the low-concentration pickling time can be selected from any value among 1.5 minutes, 2 minutes, and 2.5 minutes, and the high-concentration pickling time can be selected from any value among 0.8 minutes, 1 minute, 1.2 minutes, and 1.5 minutes.

[0029] In a preferred embodiment, the width of the shielding strip is 0.1-0.2 mm. This width range precisely covers the contour line and its stress-affected area, avoiding insufficient shielding due to being too narrow or weakening the strength of the lens body due to being too wide. Specifically, the width of the shielding strip can be selected from any value among 0.1 mm, 0.12 mm, 0.15 mm, 0.18 mm, and 0.2 mm.

[0030] In a preferred embodiment, a high-temperature resistant and ion-exchange resistant mask is prepared using photolithography or precision screen printing. Photolithography and precision screen printing enable mask preparation with micron-level precision, ensuring neat edges of the shielding band and stable shielding effect. Specifically, the photoresist can be selected from positive or negative photoresists.

[0031] In a preferred embodiment, the high-brittleness ink comprises inorganic fillers, resin, and a silane coupling agent, wherein the content of the inorganic fillers is greater than 60 wt%. The high content of inorganic fillers imparts extremely high brittleness to the ink, the silane coupling agent provides chemical bonding to the glass surface to ensure adhesion, and the resin ensures film formation. Specifically, the inorganic filler content can be selected from any value among 60%, 62%, 65%, 68%, and 70%.

[0032] In a preferred embodiment, the inorganic filler is low-temperature glass powder, and the resin is epoxy-modified silicone resin. After curing, the low-temperature glass powder forms a glassy, ​​hard, and brittle layer with extremely low elongation at break. The epoxy-modified silicone resin balances compatibility with the glass substrate and reactivity with the coupling agent. Specifically, the silane coupling agent can be selected from either aminosilanes or epoxysilanes.

[0033] In a preferred embodiment, the step of removing the mask from the chemically strengthened glass substrate includes: removing the mask by laser stripping or hot alkaline solution immersion, followed by high-pressure rinsing with pure water. Both laser stripping and hot alkaline solution immersion can efficiently and non-destructively remove the mask, while high-pressure rinsing with pure water ensures no residue affects subsequent screen printing. Specifically, the temperature of the hot alkaline solution can be selected from any value among 60°C, 70°C, and 80°C.

[0034] In one specific embodiment, a picosecond laser is used to cut the contour line of the set depth on the glass substrate. The wavelength of the picosecond laser can be selected from 1030nm and 1064nm, the dot spacing can be selected from 3μm, 4μm, 5μm and 6μm, and the cutting depth can be selected from 0.2mm, 0.25mm and 0.3mm.

[0035] In one specific embodiment, the low-concentration pickling uses hydrofluoric acid with a concentration of 4%, 5%, or 6%, and the pickling time is selected from 1.5 minutes, 2 minutes, or 2.5 minutes; the high-concentration pickling uses hydrofluoric acid with a concentration of 10%, 12%, or 14%, and the pickling time is selected from 0.8 minutes, 1 minute, 1.2 minutes, or 1.5 minutes.

[0036] In one specific embodiment, the width of the shielding strip can be selected from any one of 0.1mm, 0.12mm, 0.15mm, 0.18mm, and 0.2mm.

[0037] In one specific embodiment, the content of inorganic filler in the high brittle ink can be selected from any one of 60%, 62%, 65%, 68%, and 70%, and the silane coupling agent can be selected from any one of aminosilane and epoxysilane.

[0038] The present invention will be further described in detail below through specific embodiments: Example 1: This example provides a method for processing mobile phone camera glass.

[0039] A 0.6mm thick high-aluminosilicate glass (trade name: Gorilla Glass, purchased from Corning) is cut and polished on both sides to 0.5mm with a surface roughness Ra≤0.02μm to obtain a glass substrate.

[0040] Using a 1064nm infrared picosecond laser (purchased from Han's Laser), with a dot spacing of 5μm, 24 outer edge contour lines of the finished lens were cut on the surface of the glass substrate, with a cutting depth of 0.25mm.

[0041] The glass substrate was polished and acid-washed for 4.5 minutes with 9% hydrofluoric acid (analytical grade, Sinopharm Group), and then rinsed with water.

[0042] A high-temperature resistant, ion-exchange resistant negative photoresist (trade name: AZ 15 nXT, purchased from Merck) is coated along the contour line using a precision screen printing process to form a continuous shielding band with a width of 0.15 mm, and then cured.

[0043] The glass substrate with shielding strip was chemically strengthened by immersing it in pure KNO3 molten salt (analytical grade, Sinopharm Group) at 400℃ for 4 hours.

[0044] The photoresist was removed by soaking in hot alkaline solution (10% NaOH solution, Sinopharm Group), and the shielding strip was removed by high-pressure rinsing with pure water.

[0045] Three layers of screen printing were applied to the glass substrate: the first layer used conventional ink (trade name: SEC 123, purchased from Seiko Epson, composition: 20% pigment, 70% polyurethane resin, 10% solvent) for partial screen printing; the second layer used conventional ink for partial screen printing; the third layer used high-brittleness ink for full-surface screen printing, cured at 150℃ for 30 minutes. The high-brittleness ink consisted of: 65% low-temperature glass powder (purchased from Nippon Denka), 30% epoxy-modified silicone resin (purchased from Wacker Chemie), 5% aminosilane coupling agent (purchased from Momentive), and the balance being solvent.

[0046] The lens is separated by applying external force to the contour area of ​​the ejector pin of an automatic lens cleaver to obtain the finished lens.

[0047] Example 2: This example provides a method for processing mobile phone camera glass.

[0048] A 0.6mm thick high-aluminosilicate glass (trade name: Gorilla Glass, purchased from Corning) is cut and polished on both sides to 0.5mm with a surface roughness Ra≤0.02μm to obtain a glass substrate.

[0049] Using a 1064nm infrared picosecond laser (purchased from Han's Laser), with a dot spacing of 5μm, 24 outer edge contour lines of the finished lens were cut on the surface of the glass substrate, with a cutting depth of 0.25mm.

[0050] The glass substrate was polished and acid-washed for 4.5 minutes with 9% hydrofluoric acid (analytical grade, Sinopharm Group), and then rinsed with water.

[0051] A high-temperature resistant, ion-exchange resistant negative photoresist (trade name: AZ 15 nXT, purchased from Merck) is coated along the contour line using a precision screen printing process to form a continuous shielding band with a width of 0.15 mm, and then cured.

[0052] The glass substrate with shielding strip was chemically strengthened by immersing it in pure KNO3 molten salt (analytical grade, Sinopharm Group) at 400℃ for 4 hours.

[0053] The photoresist was removed by soaking in hot alkaline solution (10% NaOH solution, Sinopharm Group), and the shielding strip was removed by high-pressure rinsing with pure water.

[0054] Three layers of screen printing were applied to the glass substrate: the first layer used conventional ink (trade name: SEC 123, purchased from Seiko Epson, composition: 20% pigment, 70% polyurethane resin, 10% solvent) for spot screen printing; the second layer used conventional ink for spot screen printing; the third layer used conventional toughening ink for full-surface screen printing, cured at 150℃ for 30 minutes. The composition of the conventional toughening ink is: 20% pigment, 70% polyurethane resin, 10% solvent.

[0055] The lens is separated by applying external force to the contour area of ​​the ejector pin of an automatic lens cleaver to obtain the finished lens.

[0056] Example 3: This example provides a method for processing mobile phone camera glass.

[0057] A 0.6mm thick high-aluminosilicate glass (trade name: Gorilla Glass, purchased from Corning) is cut and polished on both sides to 0.5mm with a surface roughness Ra≤0.02μm to obtain a glass substrate.

[0058] Using a 1064nm infrared picosecond laser (purchased from Han's Laser), with a dot spacing of 5μm, 24 outer edge contour lines of the finished lens were cut on the surface of the glass substrate, with a cutting depth of 0.25mm.

[0059] A two-step pickling process is employed: first, pickling is performed by agitation with 5% hydrofluoric acid (analytical grade, Sinopharm Group) for 2 minutes, followed by pickling with 12% hydrofluoric acid (analytical grade, Sinopharm Group) for 1 minute, and then rinsing with clean water.

[0060] A high-temperature resistant, ion-exchange resistant negative photoresist (trade name: AZ 15 nXT, purchased from Merck) is coated along the contour line using a precision screen printing process to form a continuous shielding band with a width of 0.15 mm, and then cured.

[0061] The glass substrate with shielding strip was chemically strengthened by immersing it in pure KNO3 molten salt (analytical grade, Sinopharm Group) at 400℃ for 4 hours.

[0062] The photoresist was removed by soaking in hot alkaline solution (10% NaOH solution, Sinopharm Group), and the shielding strip was removed by high-pressure rinsing with pure water.

[0063] Three layers of screen printing were applied to the glass substrate: the first layer used conventional ink (trade name: SEC 123, purchased from Seiko Epson, composition: 20% pigment, 70% polyurethane resin, 10% solvent) for partial screen printing; the second layer used conventional ink for partial screen printing; the third layer used high-brittleness ink for full-surface screen printing, cured at 150℃ for 30 minutes. The high-brittleness ink consisted of: 65% low-temperature glass powder (purchased from Nippon Denka), 30% epoxy-modified silicone resin (purchased from Wacker Chemie), 5% aminosilane coupling agent (purchased from Momentive), and the balance being solvent.

[0064] The lens is separated by applying external force to the contour area of ​​the ejector pin of an automatic lens cleaver to obtain the finished lens.

[0065] Comparative Example 1: This comparative example provides a method for processing mobile phone camera glass.

[0066] The difference from Example 1 is that this comparative example did not perform local stress shielding, and the entire surface screen printing used conventional tough ink.

[0067] A 0.6mm thick high-aluminosilicate glass (trade name: Gorilla Glass, purchased from Corning) is cut and polished on both sides to 0.5mm with a surface roughness Ra≤0.02μm to obtain a glass substrate.

[0068] Using a 1064nm infrared picosecond laser (purchased from Han's Laser), with a dot spacing of 5μm, 24 outer edge contour lines of the finished lens were cut on the surface of the glass substrate, with a cutting depth of 0.25mm.

[0069] The glass substrate was polished and acid-washed for 4.5 minutes with 9% hydrofluoric acid (analytical grade, Sinopharm Group), and then rinsed with water.

[0070] The entire glass sheet was directly immersed in pure KNO3 molten salt (analytical grade, Sinopharm Group) at 400℃ for 4 hours for chemical strengthening, without masking.

[0071] Three layers of screen printing were applied to the glass substrate: the first layer used conventional ink (trade name: SEC 123, purchased from Seiko Epson, composition: 20% pigment, 70% polyurethane resin, 10% solvent) for partial screen printing; the second layer used conventional ink for partial screen printing; the third layer used conventional toughness ink (composition: 20% pigment, 70% polyurethane resin, 10% solvent) for full-surface screen printing, and cured at 150℃ for 30 minutes.

[0072] The lens is separated by applying external force to the contour area of ​​the ejector pin of an automatic lens cleaver to obtain the finished lens.

[0073] Comparative Example 2: This comparative example provides a method for processing mobile phone camera glass.

[0074] The difference from Example 1 is that: this comparative example did not perform local stress shielding, the pickling was carried out in two steps, and the entire surface screen printing used conventional tough ink.

[0075] A 0.6mm thick high-aluminosilicate glass (trade name: Gorilla Glass, purchased from Corning) is cut and polished on both sides to 0.5mm with a surface roughness Ra≤0.02μm to obtain a glass substrate.

[0076] Using a 1064nm infrared picosecond laser (purchased from Han's Laser), with a dot spacing of 5μm, 24 outer edge contour lines of the finished lens were cut on the surface of the glass substrate, with a cutting depth of 0.25mm.

[0077] A two-step pickling process is employed: first, pickling is performed by agitation with 5% hydrofluoric acid (analytical grade, Sinopharm Group) for 2 minutes, followed by pickling with 12% hydrofluoric acid (analytical grade, Sinopharm Group) for 1 minute, and then rinsing with clean water.

[0078] The entire glass sheet was directly immersed in pure KNO3 molten salt (analytical grade, Sinopharm Group) at 400℃ for 4 hours for chemical strengthening, without masking.

[0079] Three layers of screen printing were applied to the glass substrate: the first layer used conventional ink (trade name: SEC 123, purchased from Seiko Epson, composition: 20% pigment, 70% polyurethane resin, 10% solvent) for partial screen printing; the second layer used conventional ink for partial screen printing; the third layer used conventional toughness ink (composition: 20% pigment, 70% polyurethane resin, 10% solvent) for full-surface screen printing, and cured at 150℃ for 30 minutes.

[0080] The lens is separated by applying external force to the contour area of ​​the ejector pin of an automatic lens cleaver to obtain the finished lens.

[0081] Comparative Example 3: This comparative example provides a method for processing mobile phone camera glass.

[0082] The difference from Example 1 is that this comparative example has local stress shielding, but the entire surface screen printing uses conventional tough ink.

[0083] A 0.6mm thick high-aluminosilicate glass (trade name: Gorilla Glass, purchased from Corning) is cut and polished on both sides to 0.5mm with a surface roughness Ra≤0.02μm to obtain a glass substrate.

[0084] Using a 1064nm infrared picosecond laser (purchased from Han's Laser), with a dot spacing of 5μm, 24 outer edge contour lines of the finished lens were cut on the surface of the glass substrate, with a cutting depth of 0.25mm.

[0085] The glass substrate was polished and acid-washed for 4.5 minutes with 9% hydrofluoric acid (analytical grade, Sinopharm Group), and then rinsed with water.

[0086] A high-temperature resistant, ion-exchange resistant negative photoresist (trade name: AZ 15 nXT, purchased from Merck) is coated along the contour line using a precision screen printing process to form a continuous shielding band with a width of 0.15 mm, and then cured.

[0087] The glass substrate with shielding strip was chemically strengthened by immersing it in pure KNO3 molten salt (analytical grade, Sinopharm Group) at 400℃ for 4 hours.

[0088] The photoresist was removed by soaking in hot alkaline solution (10% NaOH solution, Sinopharm Group), and the shielding strip was removed by high-pressure rinsing with pure water.

[0089] Three layers of screen printing were applied to the glass substrate: the first layer used conventional ink (trade name: SEC 123, purchased from Seiko Epson, composition: 20% pigment, 70% polyurethane resin, 10% solvent) for partial screen printing; the second layer used conventional ink for partial screen printing; the third layer used conventional toughness ink (composition: 20% pigment, 70% polyurethane resin, 10% solvent) for full-surface screen printing, and cured at 150℃ for 30 minutes.

[0090] The lens is separated by applying external force to the contour area of ​​the ejector pin of an automatic lens cleaver to obtain the finished lens.

[0091] To objectively evaluate the performance differences in cleavage yield, mechanical strength, and ink adhesion of the finished lenses prepared in Examples 1-3 and Comparative Examples 1-3, and to verify the individual technical effects and synergistic effects of local stress shielding, high-brittleness ink, and two-step pickling, the following performance tests were conducted on the finished lenses: Splitting force (N): The maximum pressure value of the ejector pin when a single lens is successfully separated using an automatic sharding machine, and the average value of 50 samples is taken.

[0092] Edge chipping size (μm): The maximum edge chipping width of the outer edge of the lens after the fragment is cracked is measured using a super depth-of-field microscope, and the average value of the maximum values ​​of 50 samples is taken.

[0093] Chemical strengthening stress: The compressive stress (CS) on the surface of the lens body is measured using a surface stress meter.

[0094] Ink adhesion: Tested according to the Cross-cut test standard ASTM D3359. 3M tape was applied and then quickly peeled off to evaluate the adhesion between the ink and the glass. 5B indicates that the cut edge is completely smooth and no cells have fallen off.

[0095] Table 1 Test results of the examples and comparative examples

[0096] As shown in Table 1, Comparative Example 1, serving as the benchmark for existing technologies, exhibits a high fracturing force of 85.2 N and a chipping edge size of 35.6 μm. Comparative Example 2, without stress shielding, only optimizes the pickling process to a two-step method, resulting in almost no improvement in the fracturing force (83.5 N) and chipping edge size (34.2 μm). This aligns with common physics: under high-pressure stress-locked crack conditions, the expansion of microcrack openings has limited significance in reducing fracture resistance.

[0097] After introducing local stress shielding, the data from Comparative Example 3 and Example 2 show that the cracking force drops sharply to 42.5 N and the chipping size decreases to 18.7 μm. This proves that eliminating compressive stress closure in the contour region is the core mechanism for solving the problem of crack chipping, and the artificially created "stress trough" effectively guides the crack to break instantaneously along a predetermined trajectory.

[0098] Under the premise of stress shielding, comparing Example 1 and Comparative Example 3 (or Example 2), when the final layer of screen printing was replaced with a high-brittleness ink instead of a conventional tough ink, the fracturing force decreased slightly from 42.5N to 40.1N, but the chipping size decreased significantly from 18.7μm to 8.2μm. This proves that the simultaneous brittle fracture of the high-brittleness ink eliminates the bridging tensile force of the tough ink, which is the second major key factor in suppressing micro-chipping and edge whitening.

[0099] Example 3 combines three key elements: localized stress shielding, two-step pickling, and highly brittle ink. The cracking force is further reduced to 35.2 N, and the chipping size reaches an extremely low 3.5 μm. Comparing Examples 1 and 3, the addition of two-step pickling on top of stress shielding significantly reduces the cracking force by 4.9 N. This demonstrates that the effect of two-step pickling in expanding microcrack openings must be synergistic with stress shielding to be fully realized. Simultaneously, the bulk CS compressive stress in all examples and comparative examples remains at a high level of 746-752 MPa, and the ink adhesion reaches the highest 5B level. This indicates that the process improvement in this application significantly improves the cracking yield without affecting the lens strength or ink adhesion.

Claims

1. A method for processing mobile phone camera glass, characterized in that, Includes the following steps: Cut a contour line of a predetermined depth on a glass substrate; A high-temperature resistant and ion-exchange resistant mask is prepared along the outline region to form a shielding strip; the glass substrate with the mask is placed in molten salt for chemical strengthening; Remove the mask from the chemically strengthened glass substrate; A multi-layer screen printing process is performed on the glass substrate, with the final layer using highly brittle ink for full-surface screen printing; an external force is applied along the outline to separate the substrate and obtain the finished lens.

2. The mobile phone camera glass processing method according to claim 1, characterized in that, The specified depth contour line is cut out on the glass substrate using a picosecond laser dot-mapping method.

3. The mobile phone camera glass processing method according to claim 1, characterized in that, After cutting out the contour line at the set depth and before preparing the mask, the process includes a two-step acid pickling process: low-concentration acid pickling and high-concentration acid pickling of the glass substrate.

4. The mobile phone camera glass processing method according to claim 3, characterized in that, The low-concentration pickling uses hydrofluoric acid with a concentration of 4-6%, and the high-concentration pickling uses hydrofluoric acid with a concentration of 10-14%. The high-concentration pickling time is controlled within 1.5 minutes, and the increase in etching depth caused by the high-concentration pickling does not exceed 10 μm.

5. The mobile phone camera glass processing method according to claim 1, characterized in that, The width of the shielding strip is 0.1-0.2 mm.

6. The mobile phone camera glass processing method according to claim 1, characterized in that, The high-temperature resistant and ion-exchange resistant mask is prepared using photolithography or precision screen printing.

7. The mobile phone camera glass processing method according to claim 1, characterized in that, The brittle ink comprises inorganic fillers, resins, and silane coupling agents, wherein the content of the inorganic fillers is greater than 60 wt%.

8. The mobile phone camera glass processing method according to claim 7, characterized in that, The inorganic filler is low-temperature glass powder, and the resin is epoxy-modified silicone resin.

9. The mobile phone camera glass processing method according to claim 1, characterized in that, The steps for removing the mask from the chemically strengthened glass substrate include: removing the mask by laser stripping or hot alkaline solution immersion, and rinsing with pure water under high pressure.

10. The application of a glass lens prepared by the processing method according to any one of claims 1-9 in a protective lens for a mobile phone camera.